2022
DOI: 10.1039/d2cp02594a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid surface reconstruction strategies for oxygen evolution reactions: chemical grafting of MXene quantum dots on Ni–Co layered double hydroxides

Abstract: The surface reconstruction of transition metal-based catalysts with its specific catalytic mechanism is currently one of the hotspots and difficulties in the electrocatalytic oxygen evolution reaction (OER). Herein, a chemical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Although the overpotential of NiFe LDH@CDs-200 may not be as good as the other Ni-based LDH catalysts, its Tafel slope was quite small (Table S2 †). 33,[41][42][43][44][45][46][47][48][49][50] A lower Tafel slope means that the overpotential does not increase rapidly with the current density, which indicated that NiFe LDH@CDs-200 was comparable to other catalysts at high current density. It is supposed that the CDs work like a 'electron transportation bridge' to suppress the recombination of photogenerated electron-hole pairs, reflected in the lower overpotential and Tafel slope.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…Although the overpotential of NiFe LDH@CDs-200 may not be as good as the other Ni-based LDH catalysts, its Tafel slope was quite small (Table S2 †). 33,[41][42][43][44][45][46][47][48][49][50] A lower Tafel slope means that the overpotential does not increase rapidly with the current density, which indicated that NiFe LDH@CDs-200 was comparable to other catalysts at high current density. It is supposed that the CDs work like a 'electron transportation bridge' to suppress the recombination of photogenerated electron-hole pairs, reflected in the lower overpotential and Tafel slope.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…In addition, another study speculated that in an alkaline environment, MXene-based materials may also have unconventional bifunctional mechanism (BM) in addition to the above-mentioned AEM and LOM, involving the production of *OO and *H, but this has not been confirmed and needs to be further studied. 55…”
Section: Reaction Mechanisms Of Hydrogen and Oxygen Production By Wat...mentioning
confidence: 99%
“…In addition, another study speculated that in an alkaline environment, MXene-based materials may also have unconventional bifunctional mechanism (BM) in addition to the above-mentioned AEM and LOM, involving the production of *OO and *H, but this has not been confirmed and needs to be further studied. 55 At present, many types of catalytic mechanisms have been proposed for the acidic OER, as shown in Table 1, where * represents the active sites on the catalyst surface, where the reaction mechanisms of different catalysts may be different. Among them, the most commonly recognized OER catalytic mechanisms are the electrochemical oxidation pathway and oxidation pathway.…”
Section: ãOh ! ðVmentioning
confidence: 99%
“…Many effective strategies have been carried out to enhance catalytic performance, such as dopant insertion, 5,6 defect 7,8 and heterojunction construction, 9–11 and surface interface regulation. 12,13…”
mentioning
confidence: 99%